THE IMPACT OF TRADE SUBSIDIES ON THE ENVIRONMENT: A PROBLEM FOR THE WTO TRADING SYSTEM - Singh Gurwinder (European Scientific Journal, ESJ, 2013)
The principal objective of the WTO is to promote free trade among its Member Nations. Along with this main objective are also compounded values such as sustainable development, the pursuit of which goes along with free trade. It is ironical that within the WTO trading system, there are several agreements to promote free trade, but no explicit agreement supporting environmentrelated issues on a parallel basis has been adopted. After analysing the practices followed by the Member States, it seems that trade interests are prevailing over the environmental issues, because the general description of the subsidies within the WTO framework does not cover trade advantages obtained by giving priority to the practice of trading at the cost of the environment values. Looking at this issue from the perspective of the WTO trading system, it seems that the outcome of prioritising trade at the cost of the environment is the same as the use of non-permissible subsidies for the promotion of trade. As an example, the effect of unregulated subsidies on the environment can be seen in the fisheries industry. Trade subsidies, without checks and balances have depleted several species of fish even to the level of their extinction. As the basic objective of the WTO is to promote free trade, subsidies on the contrary are being used by the Member States to compete with each other in market systems allegedly following free trade. This article attempts to explore the effect of subsidies as a consequence of free trade, which in a way takes the form of non-permissible subsidies, on the environment from two perspectives. The first, is that the principle of sustainable development is being subjugated as a result of unregulated growth in trade between Developed and Developing countries. The second, is that trading between the nations, through bilateral treaties without taking into account the environmental standards followed by the country producing the goods has led to harmful effects on the environment. Example referred is such as, the dismantling of the ships. The trade advantages sought by shifting of these industries have been compared to the monetary benefits obtained and in the specific context of this article, have been related to the actionable subsidies. Finally, this article concludes by making the suggestion that a compatible approach should be adopted so that free trade would not have negative impacts for environmental standards. Free trade is distributing money but damaging the wealth of nature